Ruthenium (Ru) Doped Titanium Dioxide (P25) Electrode for Dye Sensitized Solar Cells - Rajaramanan, T.; Natarajan, M.; Ravirajan, P.; Senthilnanthanan, M.; Velauthapillai, D. (MDPI, 2020)
In this study, P25-titanium dioxide (TiO2) was doped with ruthenium (Ru) by systematically varying the Ru content at 0.15, 0.30, 0.45 and 0.6 mol%. The synthesized Ru-doped TiO2 nanomaterials have been characterized by X-ray diffraction (XRD), Raman spectroscopy, energy-dispersive X-ray (EDX) analysis, UV-visible (UV–Vis) spectroscopy, and electrochemical impedance (EIS) spectroscopy. The XRD patterns of undoped and Ru-doped TiO2 nanomaterials confirm the presence of mixed anatase and rutile phases of TiO2 while EDX spectrum confirms the presence of Ti, O and Ru. Further, UV-visible absorption spectra of doped TiO2 nanomaterial reveal a slight red shift on Ru-doping. The short circuit current density (JSC) of the cells fabricated using the Ru-doped TiO2 photoanode was found to be dependent on the amount of Ru present in TiO2. Optimized cells with 0.3 mol% Ru-doped TiO2 electrodes showed efficiency which is 20% more than the efficiency of the control cell (η = 5.8%) under stimulated illumination (100 mWcm−2 , 1 sun) with AM 1.5 filter. The increase in JSC resulted from the reduced rate of recombination upon doping of Ru and this was confirmed by EIS analysis.
Keywords: Dye sensitized solar cells; Ru-doped TiO2; P25-TiO2